Patterns of urinary cortisol levels during ontogeny appear population specific rather than species specific in wild chimpanzees and bonobos. Issue 147 (October 2020) - Tkaczynski, Patrick J.; Behringer, Verena; Ackermann, Corinne Y.; Fedurek, Pawel; Fruth, Barbara; Girard-Buttoz, Cédric; Hobaiter, Catherine; Lee, Sean M.; Löhrich, Therese; Preis, Anna; Samuni, Liran; Zommers, Zinta; et al.
Abstract: Compared with most mammals, postnatal development in great apes is protracted, presenting both an extended period of phenotypic plasticity to environmental conditions and the potential for sustained mother-offspring and/or sibling conflict over resources. Comparisons of cortisol levels during ontogeny can reveal physiological plasticity to species or population specific socioecological factors and in turn how these factors might ameliorate or exaggerate mother-offspring and sibling conflict. Here, we examine developmental patterns of cortisol levels in two wild chimpanzee populations (Budongo and Taï), with two and three communities each, and one wild bonobo population (LuiKotale), with two communities. Both species have similar juvenile life histories. Nonetheless, we predicted that key differences in socioecological factors, such as feeding competition, would lead to interspecific variation in mother-offspring and sibling conflict and thus variation in ontogenetic cortisol patterns. We measured urinary cortisol levels in 1394 samples collected from 37 bonobos and 100 chimpanzees aged up to 12 years. The significant differences in age-related variation in cortisol levels appeared population specific rather than species specific. Both bonobos and Taï chimpanzees had comparatively stable and gradually increasing cortisol levels throughout development; Budongo chimpanzees experienced declining cortisol levels before increases in later ontogeny. These age-related population differences in cortisol patterns were not explained by mother-offspring or sibling conflict specifically; instead, the comparatively stable cortisol patterns of bonobos and Taï chimpanzees likely reflect a consistency in experience of competition and the social environment compared with Budongo chimpanzees, where mothers may adopt more variable strategies related to infanticide risk and resource availability. The clear population-level differences within chimpanzees highlight potential intraspecific flexibility in developmental processes in apes, suggesting the flexibility and diversity in rearing strategies seen in humans may have a deep evolutionary history.